Impairment of Tomato WAT1 Enhances Resistance to Vascular Wilt Fungi Despite Severe Growth Defects - Hanika, Katharina; Schipper, Danny; Chinnappa, Shravya; Oortwijn, Marian; Schouten, Henk J.; Thomma, Bart P. H. J.; Bai, Yuling (Frontiers in Plant Science, 2021)
Verticillium dahliae is a particularly notorious vascular wilt pathogen of tomato and poses a reoccurring challenge to crop protection as limited qualitative resistance is available. Therefore, alternative approaches for crop protection are pursued. One such strategy is the impairment of disease susceptibility (S) genes, which are plant genes targeted by pathogens to promote disease development. In Arabidopsis and cotton, the Walls Are Thin 1 (WAT1) gene has shown to be a S gene for V. dahliae. In this study, we identified the tomato WAT1 homolog Solyc04g080940 (SlWAT1). Transient and stable silencing of SlWAT1, based on virus-induced gene silencing (VIGS) and RNAi, respectively, did not consistently lead to reduced V. dahliae susceptibility in tomato. However, CRISPR-Cas9 tomato mutant lines carrying targeted deletions in SlWAT1 showed significantly enhanced resistance to V. dahliae, and furthermore also to V. albo-atrum and Fusarium oxysporum f. sp. lycopersici (Fol). Unfortunately these tomato CRISPR mutant lines suffered from severe growth defects. Disabling the tomato WAT1 gene resulted in broad-spectrum resistance to various vascular pathogens in tomato. In order to overcome the pleiotropic effect caused by the impairment of the tomato WAT1 gene, future efforts should be devoted to identifying tomato SlWAT1 mutant alleles that do not negatively impact tomato growth and development.